Applied Decision-Making Applications in Computer Sciences and Engineering - Sanchez, Mauricio A.; Aguilar, Leocundo; Castañón-Puga, Manuel; Rodríguez, Antonio (Studies in Systems, Decision and Control, 2019)
This book gathers a collection of the latest research, applications, and proposals, introducing readers to innovations and concepts from diverse environments and systems. As such, it will provide students and professionals alike with not only cutting-edge information, but also new inspirations and potential research directions. Each chapter focuses on a specific aspect of applied decision making, e.g. in complex systems, computational intelligence, security, and ubiquitous computing. .